Environmental DNA (eDNA) metabarcoding and fish visual census reveals the first record of Doboatherina magnidentata in the Philippines - JOHN ARLU BAUTISTA; JANECE JEAN MANUBAG; NANETTE HOPE SUMAYA; JOEY GENEVIEVE MARTINEZ; SHARON ROSE TABUGO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Bautista JA, Manubag JJ, Sumaya NH, Martinez JG, Tabugo SR. 2023. Environmental DNA (eDNA) metabarcoding and fish visual census reveals the first record of Doboatherina magnidentatain the Philippines. Biodiversitas 24: 3063-3072. Biodiversity monitoring is the cornerstone for conserving marine fish species. However, classical methods, like the Fish Visual Census (FVC), are often limited due to sampling difficulties, the occurrence of rare and cryptic organisms, and reliance on a taxonomic expert for species identification. Recently, environmental DNA (eDNA) metabarcoding has been suggested as a non-invasive, powerful tool for biomonitoring. This study evaluates the eDNA approach as complementary tool for the FVC data in species detection and identification of important marine fishes from the marine sanctuary of Dalipuga, Iligan City, Philippines. The findings obtained through the eDNA approach provide insights into identifying significant fish species. Notably, the presence of the Hippocampus kuda Bleeker, 1852 (yellow seahorse), categorized as a vulnerable and threatened species, was detected. Additionally, the study identified Herklotsichthys quadrimaculatus Rüppell, 1837 (bluestripe herring), a native species to the Philippines that may pose potential risks to humans and the ecological balance. Furthermore, two demersal fish species, namely Large-scale whiting (Sillaginops macrolepis Bleeker, 1858) and Large-scale mullet (Planiliza macrolepis Smith, 1846), were also detected. The eDNA approach also delineated the morphologically cryptic fishes from Scaridae (parrotfishes) and Mugilidae (mullet fish) taxa to the species level. The highlight of this study was the detectionof the new Indo-pacific atherinomorine fish species Doboatherina magnidentata, which to the best of our knowledge, was the first record in the Philippine marine waters. Despite the efficiency of the eDNA metabarcoding in fish species detection and identification, the viability of eDNA in the marine environment and biases of the primer limit this method. Thus, the classical method must complement the molecular approach for better taxonomic resolution and community analysis. Future studies were also recommended to use a multigene eDNA approach to improve taxonomic sensitivity and reduce primer biases.